High-strength hot-dip galvanized steel sheet with excellent plating property and method for manufacturing the same
Patent Information
- Application Number
- CN202180085903.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-18
- Filing Date
- 2021-12-09
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-12-09
AI Technical Summary
[0003]为了汽车用钢板的高强度化,通常在钢中添加大量的Si、Mn、Al等元素以增加强度,包含这些元素的钢板在退火热处理过程中由于所述元素在钢板的表面上生成氧化物,将钢板浸入熔融锌镀浴中时镀覆性变差,并且可能会引起镀覆剥离
[0015]根据本发明的一个方面,可以提供一种镀覆性优异的高强度热浸镀锌钢板及其制造方法。
Smart Images

Figure CN116648525B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a high-strength hot-dip galvanized steel sheet with excellent coating properties and its manufacturing method. Background Technology
[0002] The demand for ultra-high-strength steel sheets has surged due to recent environmental regulations aimed at addressing stricter fuel efficiency and crash stability controls on automobiles. Furthermore, countries need to improve fuel efficiency to achieve carbon reduction targets, while the increasing weight of vehicles due to higher performance and various convenience features further fuels the growing demand for ultra-high-strength steel sheets. Therefore, steel companies are focusing on developing high-strength steel sheets such as dual-phase (DP) steel, transformation-induced plasticity (TRIP) steel, and complex-phase (CP) steel.
[0003] To increase the strength of steel sheets used in automobiles, large amounts of elements such as Si, Mn, and Al are typically added to the steel. However, during annealing heat treatment, these elements form oxides on the surface of the steel sheet, leading to poor plating properties when immersed in a molten zinc plating bath, and potentially causing plating peeling. Furthermore, during subsequent spot welding, liquid metal embrittlement (liquid metal embrittlement) may occur, causing cracks as molten metal penetrates to the grain boundaries of the base metal, further impairing spot weldability.
[0004] To improve the plating properties of steel sheets with a large amount of added Si, Mn, and Al, it is necessary to suppress the formation of oxides on the surface of the steel sheet. This requires reducing the amount of Si and Al added to the steel, but in this case, it is difficult to ensure the desired material.
[0005] A representative technology for solving this problem includes Patent Document 1. Patent Document 1 relates to a technique that suppresses the formation of Si oxides and the like on the surface by adding trace amounts of Sb to steel to preferentially enrich it in the grain boundaries.
[0006] However, when manufacturing steel plates, there is still a need to develop a technology that can more reliably prevent the diffusion of alloying elements in steel.
[0007] [Existing Technical Documents]
[0008] (Patent Document 1) Japanese Patent Publication No. 6222040 Summary of the Invention
[0009] Technical problems to be solved
[0010] One aspect of the present invention is to provide a high-strength hot-dip galvanized steel sheet with excellent coating properties and a method for manufacturing the same.
[0011] Technical solution
[0012] One embodiment of the present invention provides a high-strength hot-dip galvanized steel sheet with excellent coating properties, having a base steel sheet and a hot-dip galvanized layer formed on one or both sides of the base steel sheet. The base steel sheet, by weight percent, comprises: carbon (C): 0.1-0.3%, silicon (Si): 0.1-2.0%, aluminum (Al): 0.1-1.5%, manganese (Mn): 1.5-3.0%, the balance being Fe and unavoidable impurities. The sum of Si and Al satisfies 1.2-3.5%, the Al / Si ratio satisfies 0.5 to 2.0, the surface roughness (Ra) of the base steel sheet is 0.5 μm or more, and an internal oxide layer with a thickness of less than 4 μm is included directly beneath the surface of the base steel sheet.
[0013] Another embodiment of the present invention provides a method for manufacturing a high-strength hot-dip galvanized steel sheet with excellent coating properties, comprising the following steps: reheating a slab at 1000-1300°C, wherein the slab comprises, by weight %,: carbon (C): 0.1-0.3%, silicon (Si): 0.1-2.0%, aluminum (Al): 0.1-1.5%, manganese (Mn): 1.5-3.0%, the balance being Fe and unavoidable impurities, wherein the Si and Al The sum of Al and Si must be greater than 1.2%, and the Al / Si ratio must be between 0.5 and 2.0. The reheated slab is hot-rolled at 800-950°C to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is coiled at 630-700°C. The coiled hot-rolled steel sheet is pickled for more than 30 seconds and less than 60 seconds. The pickled hot-rolled steel sheet is cold-rolled, annealed, and cooled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is hot-dip galvanized.
[0014] Beneficial effects
[0015] According to one aspect of the present invention, a high-strength hot-dip galvanized steel sheet with excellent coating properties and a method for manufacturing the same can be provided. Attached Figure Description
[0016] Figure 1 This is a photograph of the surface of Invention Example 1 according to an embodiment of the present invention.
[0017] Figure 2 This is a photograph of the surface of Comparative Example 4 according to an embodiment of the present invention.
[0018] Figure 3The image shows a cross-section of a cold-rolled steel sheet according to an embodiment of the present invention, as observed using a scanning electron microscope (SEM).
[0019] Figure 4 The image shows a cross-section of a cold-rolled steel sheet of Comparative Example 4, as observed using a scanning electron microscope (SEM) according to an embodiment of the present invention.
[0020] Best practice
[0021] The following describes a high-strength hot-dip galvanized steel sheet with excellent coating properties according to an embodiment of the present invention. The hot-dip galvanized steel sheet of the present invention comprises a base steel sheet and a hot-dip galvanized layer formed on one or both sides of the base steel sheet. First, the alloy composition of the base steel sheet of the present invention will be described. Unless otherwise stated, the alloy composition content described below is expressed as weight %.
[0022] Carbon (C): 0.1-0.3%
[0023] The carbon (C) is an element that contributes to the stabilization of the austenitic structure; as the C content increases, it helps to ensure the austenitic structure. To achieve the above effect, the C content is preferably 0.1% or more. However, when the C content exceeds 0.3%, defects may occur in the cast billet, and weldability may also decrease. Therefore, the C content is preferably in the range of 0.1-0.3%. The lower limit of the C content is more preferably 0.15%. The upper limit of the C content is more preferably 0.25%.
[0024] Silicon (Si): 0.1-2.0%
[0025] Silicon (Si) is an element that helps stabilize retained austenite by inhibiting the precipitation of carbides in ferrite and promoting the diffusion of carbon from ferrite to austenite. To achieve these effects, the Si content is preferably 0.1% or more. When the Si content exceeds 2.0%, rollability deteriorates, and oxides form on the surface of the steel sheet during heat treatment, which may lead to poor plating and adhesion. Therefore, the Si content is preferably in the range of 0.1-2.0%. The lower limit of the Si content is more preferably 0.2%. The upper limit of the Si content is more preferably 1.8%.
[0026] Aluminum (Al): 0.1-1.5%
[0027] Aluminum (Al) is an element that combines with oxygen in steel to act as a deoxidizer. Furthermore, like Si, Al is an element that inhibits the formation of carbides in ferrite and helps stabilize retained austenite. To achieve these effects, Al is preferably added at 0.1% or more. When the Al content exceeds 1.5%, the slab's strength deteriorates, and Al is an element with a strong affinity for oxygen, thus forming oxides on the surface of the steel sheet, which may hinder plating and adhesion. Therefore, the Al content is preferably in the range of 0.1-1.5%. The lower limit of the Al content is more preferably 0.2%. The upper limit of the Al content is more preferably 1.4%.
[0028] Manganese (Mn): 1.5-3.0%
[0029] Like carbon, Mn is an element that stabilizes austenitic structures. When the Mn content is less than 1.5%, it is difficult to ensure the target strength due to the ferrite phase transformation. When the Mn content exceeds 3.0%, martensite forms due to the delayed phase transformation during secondary annealing heat treatment, making it difficult to ensure the desired ductility. Therefore, the Mn content is preferably in the range of 1.5-3.0%. The lower limit of the Mn content is more preferably 1.7%. The upper limit of the Mn content is more preferably 2.9%.
[0030] In addition to the steel composition described above, it may contain a balance of Fe and other unavoidable impurities. Undesirable impurities are inevitably introduced during conventional steel manufacturing processes, and therefore cannot be completely eliminated; this meaning is easily understood by those skilled in the art of steel manufacturing. Furthermore, this invention does not completely exclude the addition of other components besides the steel composition described above.
[0031] Furthermore, as mentioned above, both Si and Al are elements that contribute to stabilizing retained austenite. To effectively achieve this, the sum of the contents of Si and Al is preferably in the range of 1.2-3.5%. When the sum of the contents of Si and Al is less than 1.2%, it is difficult to sufficiently obtain the effect of increasing elongation. On the other hand, when the sum of the contents of Si and Al exceeds 3.5%, it may cause problems with poor castability and rollability. The lower limit of the sum of the contents of Si and Al is more preferably 1.3%. The upper limit of the sum of the contents of Si and Al is more preferably 3.4%.
[0032] Furthermore, the Al / Si ratio is preferably between 0.5 and 2.0. When the Al / Si ratio is less than 0.5, the sensitivity to liquid metal embrittlement (LME) in spot welding increases due to the matrix formation of the Si base, which may lead to poor weldability. On the other hand, when the Al / Si ratio exceeds 2.0, the oxygen affinity increases relatively due to the matrix formation of the Al base, making it easier for oxides to form on the surface of the steel sheet, which may result in poor plating and adhesion. The lower limit of the Al / Si ratio is more preferably 0.6. The upper limit of the Al / Si ratio is more preferably 1.9.
[0033] The surface roughness (Ra) of the base steel plate of the hot-dip galvanized steel sheet of the present invention is preferably 0.5 μm or more. As described above, by imparting surface roughness to the base steel plate, adhesion can be ensured through the anchoring effect between the hot-dip galvanized layer and the base steel plate. To obtain the above effect, the surface roughness (Ra) of the base steel plate is preferably 0.5 μm or more. The surface roughness (Ra) of the base steel plate is more preferably 0.7 μm or more. Furthermore, in the present invention, as the surface roughness of the base steel plate increases, it is beneficial to ensure the above effect, so there is no particular upper limit. However, due to limitations in the manufacturing process, the surface roughness of the base steel plate may be difficult to exceed 2 μm.
[0034] The hot-dip galvanized steel sheet of the present invention preferably includes an internal oxide layer with a thickness of less than 4 μm directly beneath the surface of the base steel sheet. A feature of the present invention is that by forming an internal oxide layer directly beneath the surface of the base steel sheet, it prevents the diffusion of Al or Si present in the base steel sheet to the surface portion of the steel sheet and prevents the formation of Al or Si oxides on the surface portion, thereby improving the coating properties. However, when the thickness of the internal oxide layer is 4 μm or more, the oxides on the surface of the steel sheet are rolled up during the annealing heat treatment, thus having the disadvantage of potentially causing surface defects such as dents. Therefore, the thickness of the internal oxide layer is preferably less than 4 μm. More preferably, the thickness of the internal oxide layer is 3.5 μm or less.
[0035] The internal oxide layer may contain oxides with a maximum length of less than 4 μm. When the maximum length of the oxides is 4 μm or more, the oxides on the surface of the steel plate are rolled up during the annealing heat treatment, which may result in surface defects such as dents. Therefore, the maximum length of the oxides is preferably less than 4 μm. More preferably, the maximum length of the oxides is 3.5 μm or less.
[0036] The oxide can be composed of a composite oxide of Al and Si. As described above, by making the oxide composed of a composite oxide of Al and Si, forming an oxide with a discontinuous morphology rather than a continuous morphology such as layers, an effect that improves the adhesion of the plating can be obtained.
[0037] The Al and Si composite oxide can exist within grains or at grain boundaries, but is relatively abundant at grain boundaries. In this case, the Al and Si composite oxide is preferably present intermittently at the grain boundaries. As mentioned above, the intermittent presence of the Al and Si composite oxide at grain boundaries is advantageous for ensuring plating adhesion compared to continuous presence. More specifically, among the Al contained in the Al and Si composite oxide, the Al atoms present at grain boundaries can have a spacing of 20 nm or more. When the spacing of the Al atoms present at grain boundaries is less than 20 nm, it may be difficult to ensure plating adhesion. More preferably, the spacing of the Al atoms present at grain boundaries is 30 nm or more.
[0038] The hot-dip galvanized steel sheet of the present invention, as described above, has a yield strength of 600 MPa or more, a tensile strength of 950 MPa or more, and an elongation of 20% or more, thereby ensuring excellent mechanical and physical properties. Furthermore, the hot-dip galvanized layer covers 95% or more of the total area of the base steel sheet while exhibiting good coating adhesion, thus providing excellent coating properties. In addition, it does not produce LME cracks, thereby providing excellent resistance to LME cracking.
[0039] The following describes a method for manufacturing a high-strength hot-dip galvanized steel sheet with excellent coating properties according to one embodiment of the present invention.
[0040] First, the slab satisfying the above alloy composition is reheated at 1000-1300°C. When the reheating temperature of the slab is below 1000°C, a significant increase in rolling load may occur; when the reheating temperature exceeds 1300°C, excessive surface oxide scale may occur. Therefore, the reheating temperature of the slab is preferably in the range of 1000-1300°C. The lower limit of the reheating temperature is more preferably 1050°C. The upper limit of the reheating temperature is more preferably 1250°C.
[0041] Subsequently, the reheated slab is hot-finished at 800-950°C to obtain a hot-rolled steel sheet. When the hot-finishing temperature is below 800°C, the rolling load increases, making rolling difficult. When the hot-finishing temperature exceeds 950°C, the increased thermal fatigue of the rolls leads to a shorter roll life. Therefore, the hot-finishing temperature is preferably in the range of 800-950°C. The lower limit of the hot-finishing temperature is more preferably 830°C. The upper limit of the hot-finishing temperature is more preferably 930°C.
[0042] The hot-rolled steel sheet is then coiled at 630-700°C. When the coiling temperature is below 630°C, the internal oxide layer is not formed, and oxide formation is promoted on the surface of the steel sheet during the annealing heat treatment, which may result in poor plating. When the coiling temperature exceeds 700°C, the depth of the internal oxide layer increases significantly, and the oxide is rolled up by the rollers during subsequent annealing heat treatment, which may cause surface defects such as dents. Therefore, the coiling temperature is preferably in the range of 630-700°C. The lower limit of the coiling temperature is more preferably 650°C. The upper limit of the coiling temperature is more preferably 680°C.
[0043] Subsequently, the coiled hot-rolled steel sheet is pickled for more than 30 seconds and less than 60 seconds. When the pickling time is less than 30 seconds, the hot-rolled oxide scale cannot be completely removed, and the residual oxide scale may cause uncoated or delamination of the coating. On the other hand, when the pickling time is more than 60 seconds, the pickling solution penetrates along the grain boundaries of the internal oxide layer and causes the internal oxide layer to fall off, resulting in the complete removal of the internal oxide layer from the final steel sheet. During the annealing heat treatment, it is impossible to suppress the diffusion of alloying elements to the surface of the steel sheet, so the coating properties and adhesion may deteriorate. Furthermore, when the pickling time is not met, since the surface roughness (Ra) of the base steel sheet is less than 0.5 μm, a smooth surface is obtained, making it difficult to expect an anchoring effect with the hot-dip galvanized layer during the subsequent coating process, and it is difficult to ensure adhesion. Therefore, the pickling time is preferably in the range of more than 30 seconds and less than 60 seconds. The lower limit of the pickling time is more preferably 35 seconds, and more preferably 40 seconds. The upper limit of the pickling time is more preferably 55 seconds, and even more preferably 50 seconds.
[0044] Subsequently, the pickled hot-rolled steel sheet is cold-rolled, annealed, and cooled to obtain a cold-rolled steel sheet. In this invention, there are no particular limitations on the conditions for cold rolling, annealing, and cooling, and conditions commonly performed in this art can be utilized.
[0045] The cooled cold-rolled steel sheet is then hot-dip galvanized. In this invention, there are no particular limitations on the hot-dip galvanizing method, and conditions commonly used in this art can be employed. However, for example, it can be carried out by immersing the cold-rolled steel sheet in a molten zinc bath at 440-460°C. When the temperature of the molten zinc bath is below 440°C, the viscosity of the bath increases, reducing the mobility of the roll winding the steel sheet and causing slippage between the steel sheet and the roll. This can potentially lead to defects in the steel sheet. When the temperature of the molten zinc bath exceeds 460°C, it promotes the dissolution of the steel sheet in the bath, accelerating the formation of dross in the form of Fe-Zn compounds, which may also lead to surface defects.
[0046] Furthermore, after hot-dip galvanizing, the process may further include an alloying heat treatment step at 480-600°C on the hot-dip galvanized steel sheet. When the alloying heat treatment temperature is below 480°C, the Fe in the base material cannot diffuse sufficiently into the coating, thus failing to adequately ensure the Fe content in the coating. When the alloying heat treatment temperature exceeds 600°C, the Fe content in the coating becomes excessive, potentially leading to coating peeling and powdering during steel sheet processing. Detailed Implementation
[0047] The present invention will now be described in more detail through embodiments. However, the following embodiments are only used to illustrate the present invention in more detail and do not limit the scope of the invention.
[0048] (Example)
[0049] Molten metal with the alloy composition described in Table 1 was formed into ingots with a width of 175 mm and a thickness of 90 mm in a vacuum melting furnace. These ingots were then reheated at 1200 °C for 1 hour for homogenization, hot-rolled at 900 °C (above Ar3), and then coiled under the conditions described in Table 2 to produce hot-rolled steel sheets. Under the conditions described in Table 2, the hot-rolled steel sheets were immersed in a 15% HCl pickling solution and pickled. Afterwards, they were cold-rolled with a cold-rolling reduction rate of 50-60% to produce cold-rolled steel sheets. The cold-rolled steel sheets were annealed in a reduction furnace at 860 °C by blowing nitrogen gas containing 5% by volume hydrogen, then cooled and immersed in a molten zinc plating bath for 5 seconds. The plating adhesion was then adjusted to 60 g / m² on one side by air wiping. 2 This level of technology enables the manufacture of hot-dip galvanized steel sheets.
[0050] After measuring the mechanical and physical properties, base steel plate roughness, internal oxide layer thickness, maximum oxide length, Al spacing at grain boundaries, coating properties, and resistance to LME cracking of the hot-dip galvanized steel sheet manufactured as described above, the results are shown in Tables 2 and 3 below. Furthermore, the oxides measured are composite oxides of Al and Si.
[0051] For mechanical and physical properties, hot-dip galvanized steel sheets were cut into 40mm×200mm sizes perpendicular to the rolling direction, the sides were milled, and tensile test pieces were manufactured according to JIS 5 standard. The yield strength (YS), tensile strength (TS) and elongation (EL) were measured using a tensile testing machine.
[0052] For the surface roughness (Ra), thickness of the internal oxide layer, and maximum length of the oxide layer of the base steel plate, 10 locations were randomly selected from the cross-sectional microstructure images obtained by scanning electron microscopy (SEM) and measured at 5000x magnification. The average values were then recorded.
[0053] The spacing of Al atoms present at grain boundaries in Al and Si composite oxides was measured by transmission electron microscopy (TEM) and composition mapping using energy dispersive spectroscopy (EDS).
[0054] The coating performance was evaluated by the following method: the area of the hot-dip galvanized layer formed relative to the total area of the hot-dip galvanized steel sheet was measured by image analysis and the score was measured. After the structural adhesive was applied to the hot-dip galvanized steel sheet, it was cured at 175°C for 20 minutes and then bent at 90° to confirm whether it adhered to the sealant (coating adhesion).
[0055] Resistance to LME cracking was evaluated by determining whether LME cracks would occur after welding hot-dip galvanized steel sheets at the upper limit current. Welding was performed using a Cu-Cr electrode with a tip diameter of 6 mm and applying a welding current at an electrode pressure of 2.6 kN for 16 cycles of energizing and 15 cycles of holding. When the steel sheet thickness was t, the welding current at which the weld nugget diameter was less than 4√t was set as the lower limit current, and the welding current at which spatter occurred was set as the upper limit current (expulsion current).
[0056] [Table 1]
[0057]
[0058] [Table 2]
[0059]
[0060]
[0061] [Table 3]
[0062]
[0063] As can be seen from Tables 1 to 3, in the case of Invention Examples 1 to 4, which meet the alloy composition and manufacturing conditions proposed in this invention, the base steel plate has excellent plating properties and resistance to LME cracking because the surface roughness, thickness of the internal oxide layer, maximum length of the oxide, and spacing of Al present at the grain boundaries are ensured.
[0064] On the other hand, it can be seen that in Comparative Example 1, the elongation rate is low because the sum of Si and Al proposed in this invention is not satisfied.
[0065] It can be seen that Comparative Example 2 has a lower Al to Si ratio than that proposed in this invention, and therefore LME cracks are generated.
[0066] It can be seen that Comparative Example 3 exceeded the Al to Si ratio proposed in this invention, resulting in a large amount of uncoated material and a deterioration in coating quality.
[0067] As can be seen, in Comparative Example 4, since the winding temperature proposed in this invention is not met, an internal oxide layer cannot be formed. Therefore, not only is there no coating, but the coating adhesion is also poor.
[0068] As can be seen, in Comparative Example 5, since the pickling speed proposed in this invention is not met, an internal oxide layer cannot be formed. Therefore, not only is there no plating, but the plating adhesion is also poor.
[0069] Figure 1 This is a photograph of the surface of Invention Example 1. Figure 2 This is a surface photograph of Comparative Example 4. (By...) Figure 1 and Figure 2 It can be seen that Invention Example 1 has almost no unplated areas, so the plating quality is good, while Comparative Example 4 has a large number of unplated areas, so the plating quality is poor.
[0070] Figure 3 The photographs are of the cross-section of the cold-rolled steel sheet of Invention Example 1, observed using a scanning electron microscope (SEM). Figure 4 These are photographs of the cross-section of the cold-rolled steel sheet in Comparative Example 3, observed using a scanning electron microscope (SEM). Figure 3 and Figure 4 It is known that the base steel plate of Invention Example 1 has an appropriate surface roughness and an internal oxide layer of appropriate thickness, but the base steel plate of Comparative Example 4 has a very low surface roughness and no internal oxide layer is formed.
Claims
1. A high-strength hot-dip galvanized steel sheet with excellent coating properties, comprising a base steel sheet and a hot-dip galvanized layer formed on one or both sides of the base steel sheet, wherein, by weight%, the base steel sheet comprises: carbon (C): 0.1-0.3%, silicon (Si): 0.1-2.0%, aluminum (Al): 0.1-1.5%, manganese (Mn): 1.5-3.0%, the balance being Fe and unavoidable impurities, wherein the sum of Si and Al satisfies 1.2-3.5%, the Al / Si ratio satisfies 0.5 to 2.0, the surface roughness Ra of the base steel sheet is 0.5 μm or more, and an internal oxide layer with a thickness of less than 4 μm is included directly below the surface of the base steel sheet.
2. The high-strength hot-dip galvanized steel sheet with excellent coating properties according to claim 1, wherein, The internal oxide layer comprises oxides with a maximum length of less than 4 μm.
3. The high-strength hot-dip galvanized steel sheet with excellent coating properties according to claim 2, wherein, The oxide is composed of a composite oxide of Al and Si.
4. The high-strength hot-dip galvanized steel sheet with excellent coating properties according to claim 3, wherein, The composite oxide of Al and Si exists intermittently at the grain boundaries.
5. The high-strength hot-dip galvanized steel sheet with excellent coating properties according to claim 4, wherein, In the Al contained in the composite oxide of Al and Si, the Al present at the grain boundaries has a spacing of more than 20 nm.
6. The high-strength hot-dip galvanized steel sheet with excellent coating properties according to claim 1, wherein, The hot-dip galvanized steel sheet has a yield strength of over 600 MPa, a tensile strength of over 950 MPa, and an elongation of over 20%.
7. The high-strength hot-dip galvanized steel sheet with excellent coating properties according to claim 1, wherein, The area of the hot-dip galvanized layer on the hot-dip galvanized steel sheet relative to the total area of the base steel sheet is more than 95%.
8. A method for manufacturing a high-strength hot-dip galvanized steel sheet with excellent coating properties as described in claim 1, comprising the following steps: The slab is reheated at 1000-1300℃. The slab contains, by weight %: carbon (C): 0.1-0.3%, silicon (Si): 0.1-2.0%, aluminum (Al): 0.1-1.5%, manganese (Mn): 1.5-3.0%, balance Fe and unavoidable impurities, wherein the sum of Si and Al is greater than 1.2%, and the Al / Si ratio is 0.5 to 2.
0. The reheated slab is hot-finished at 800-950°C to obtain hot-rolled steel sheet; The hot-rolled steel sheet is coiled at 630-700℃; The hot-rolled steel sheet that has been coiled is pickled for more than 30 seconds but less than 60 seconds; The pickled hot-rolled steel sheet is then cold-rolled, annealed, and cooled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is hot-dip galvanized.
9. The method for manufacturing high-strength hot-dip galvanized steel sheet with excellent coating properties according to claim 8, wherein, The hot-dip galvanizing step includes immersing the cold-rolled steel sheet in a molten zinc bath at 440-460°C.
10. The method for manufacturing high-strength hot-dip galvanized steel sheet with excellent coating properties according to claim 8, wherein, Following the hot-dip galvanizing step, the method further includes a step of alloying the hot-dip galvanized cold-rolled steel sheet at 480-600°C.
Citation Information
Patent Citations
Semiconductor pressure sensor
JP1987022040A
High-strength plated steel sheet having excellent plating properties, workability, and delayed fracture resistance, and method for producing same
CN107109574A
